Understanding opposition: arguments for and against a meat tax in Sweden and their effect on policy attitudes - E Ejelöv; J Larsson; S Matti; J Nässén (Environmental Research: Food Systems)
Meat taxes could reduce emissions and improve health but risks facing opposition due to concerns about fairness, effectiveness, and autonomy. While policy-specific beliefs influence attitudes, less is known about how specific arguments in the public discourse shape these beliefs and policy acceptability. This study identifies arguments from media archives and analyzes argument endorsement of Swedish voters ( N = 3233) and politicians ( N = 1253). Counter-arguments, particularly financial concerns for farmers and low-income households, are more strongly endorsed than pro-arguments. While voters and politicians show similar agreement, right-wing respondents generally support counter-arguments more than left-wing respondents. To gain broader support, a meat tax should minimize financial burdens, for example, through cost-neutral reforms or subsidies for sustainable farming. The results also indicate that most arguments relate to multiple policy-specific beliefs, suggesting that policy-specific beliefs offer limited guidance on how to improve policy design.